Whole‐Genome Sequencing of Cytogenetically Balanced Chromosome Translocations Identifies Potentially Pathological Gene Disruptions and Highlights the Importance of Microhomology in the Mechanism of Formation. Issue 2 (5th December 2016) - Nilsson, Daniel; Pettersson, Maria; Gustavsson, Peter; Förster, Alisa; Hofmeister, Wolfgang; Wincent, Josephine; Zachariadis, Vasilios; Anderlid, Britt‐Marie; Nordgren, Ann; Mäkitie, Outi; Wirta, Valtteri; Käller, Max; et al.
Abstract : We use whole genome sequencing to characterize reciprocal translocations in both healthy and affected carriers. First, we show that half the unaffected carriers harbored disruptions in recessive disease genes and in 20% of the affected individuals the phenotype was explained by disruption of a dominant disease gene. In addition, seven candidate disease genes are pinpointed by a chromosome breakpoint. Second, we analyze the breakpoint junction sequences and identify a 'mutational signature' consistent with an underlying mechanism involving template switching. ABSTRACT: Most balanced translocations are thought to result mechanistically from nonhomologous end joining or, in rare cases of recurrent events, by nonallelic homologous recombination. Here, we use low‐coverage mate pair whole‐genome sequencing to fine map rearrangement breakpoint junctions in both phenotypically normal and affected translocation carriers. In total, 46 junctions from 22 carriers of balanced translocations were characterized. Genes were disrupted in 48% of the breakpoints; recessive genes in four normal carriers and known dominant intellectual disability genes in three affected carriers. Finally, seven candidate disease genes were disrupted in five carriers with neurocognitive disabilities ( SVOPL, SUSD1, TOX, NCALD, SLC4A10 ) and one XX‐male carrier with Tourette syndrome ( LYPD6, GPC5 ). Breakpoint junction analyses revealed microhomology and small templated insertions in a substantive fraction of the analyzed translocations (17.4%; n = 4); an observation that was substantiated by reanalysis of 37 previously published translocation junctions. Microhomology associated with templated insertions is a characteristic seen in the breakpoint junctions of rearrangements mediated by error‐prone replication‐based repair mechanisms. Our data implicate that a mechanism involving template switching might contribute to the formation of at least 15% of the interchromosomal translocation events.